Enabling Circular Economy: Towards Sustainable Electronic Waste Management Regulation - Puluhulawa, Fenty; Harun, Amanda Adelina (Universitas Negeri Gorontalo, 2024)
Electronic waste contains hazardous and toxic materials which could pollute the environment and endanger humans, therefore it requires special management. In Indonesia, Law No. 18 of 2008 concerning Waste Management has not specifically regulated the management of electronic waste. This article explores how circular economy concept are applied in Indonesia's waste management laws, specifically addressing electronic waste. The results of the study found that the waste management model in Indonesia, which generally accumulates waste in Final Disposal Sites, could not be a long-term solution for electronic waste. Based on circular economy principles, every product must be utilized optimally both as a product and as an ingredient by recycling. Recycle in an economy circular also known in Law No. 18 of 2008. The recycling method needs to be applied to electronic waste, purposed to reduce pollution caused by electronic waste, as well as reduce hazardous content due to the production process. Indonesia is still lacking in terms of electronic waste regulation.